2018
DOI: 10.3201/eid2404.170190
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial Illnesses as Important Causes of Febrile Illness in Chittagong, Bangladesh

Abstract: Scrub and murine typhus are common, treatable causes of undifferentiated febrile illnesses in hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
3
25
1
Order By: Relevance
“…In spite of significant serosurveillance reports [2][3][4] and clinical recognition of cases, rickettsial fevers are only occasionally reported in literature in or from Bangladesh. 5,6 The largest series published in 2007 revealed that clinical presentation is indistinguishable from other common causes of fever like viral and enteric fevers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In spite of significant serosurveillance reports [2][3][4] and clinical recognition of cases, rickettsial fevers are only occasionally reported in literature in or from Bangladesh. 5,6 The largest series published in 2007 revealed that clinical presentation is indistinguishable from other common causes of fever like viral and enteric fevers.…”
Section: Discussionmentioning
confidence: 99%
“…5 Presence of typical eschar in scrub typhus is also an uncommon feature. 4 Routine laboratory features are inefficient to differentiate between common causes of acute fever; serology may identify the cause. Triple antigens should be done after the first week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rickettsia and Borrelia spp. are both transmitted by ticks and are among the numerous zoonotic pathogens responsible for febrile illness among humans [8,9]. Rickettsial diseases, caused by organisms of the genus Rickettsia are classi ed into three biogroups the rst bio-group is known as spotted fever group (SFG) which includes Rocky Mountain spotted fever (RMSF) caused by R. rickettsia, as well as other spotted fevers such as Boutonneuse fever (Mediterranean spotted fever, Kenya tick-bite fever, Israeli spotted fever, African tick typhus, Marseilles fever, and Indian tick typhus,) caused by several other Rickettsia species.…”
Section: Introductionmentioning
confidence: 99%